Psychoactive Substance Use and Its Relationship to Stress, Emotional State, Depressive Symptomatology, and Perceived Threat During the COVID-19 Pandemic in Mexico - Martínez-Vélez, Nora Angélica; Tiburcio, Marcela; Natera Rey, Guillermina; Villatoro Velázquez, Jorge Ameth; Arroyo-Belmonte, Miriam; Sánchez-Hernández, Graciela Yazmín; Fernández-Torres, Morise (Frontiers in Public Health, 2021)
People can increase their use of psychoactive substances in response to stressful situations as a maladaptive mechanism for reducing negative affective states. It is therefore necessary to examine changes in the use of such substances and their relationship to mental health in light of the COVID-19 pandemic. Objective: Evaluate the relationship between psychoactive substances and stress, emotional state, and symptomatology during the COVID-19 lockdown in Mexico. Method: A national survey was conducted, using the free Google Forms platform, of residents of Mexico aged 18 and older. The survey was disseminated through social media. Results: The sample comprised 4,122 individuals, mostly women (71.8%), with an age range of 18–81 years (M = 37.08, SD = 12.689), of which 46.8% were single, and 42.9% married. In general, there was a reduction in substance use during the first 2 months of the quarantine; the most commonly used substances were alcohol, tobacco, and tranquilizers. Respondents who described having greater use than before the pandemic presented greater stress, depressive symptomatology, and perceived threat than those who did not use substances. Conclusions: Respondents who did not use substances reported lower levels of stress, depressive symptomatology, impact of the coronavirus pandemic, and perception of its threat. Women reported greater stress, depressive symptomatology, and emotional intensity than men.